EFEKTIVITAS PEMBERIAN AROMATHERAPY ABDOMINAL MASSAGE TEKNIK EFFLURAGE DIBANDINGKAN DENGAN ABDOMINAL STRETCHING EXERCISE TERHADAP PENURUNAN NYERI DYSMENORRHEA PRIMER PADA REMAJA PUTRI SEKOLAH MENENGAH PERTAMA DI DENPASAR - Dewa Ayu Chintya Antari; I Made Niko Winaya; Ida Ayu Dewi Wiryanthini (Majalah Ilmiah Fisioterapi Indonesia, 2017)
ABSTRACTPrimary dysmenorrhea is cramping in lower abdomen, back pain,often with diarrhea and nausea, and unstable emotionsand often occur in age 13-15 years and happen in time 24-48 hours. It will affect functional activity teenage girlsthat needed treatment to reduce the pain. The purpose of this study was to determine the differences in the effectivenessof aromatherapy abdominal massage technique efflurage with abdominal stretching exercise in reducing pain ofprimary dysmenorrhea in teenage girls at junior high school in Denpasar. Measurement of pain using Numerical RatingScale (NRS). This research is an experiment research design with pretest and posttest group design. The studyinvolved 20 samples then divided into 2 group. Group 1 aromatherapy abdominal massage technique efflurage andgroup 2 abdominal stretching exercise. Range of pain in group 1 decrease of 2,00 and group 2 decrease of 3,50.Paired T-test result in group 1 is p=0,000 and group 2 is p=0,000. The difference between group 1 and group 2 wasobtained p=0,001. It was concluded that abdominal stretching exercise more effective to reduce the pain of primarydysmenorrhea in teenage girls junior high school in Denpasar compared with aromatherapy abdominal massagetechnique efflurage.Keywords : Primary dysmenorrhea, Aromatherapy Abdominal Massage Technique Efflurage, Abdominal Stretching Exercise, Numerical Rating Scale (NRS)